You have to drive: Impacts of planning policies on urban form and mobility behavior in Kuala Lumpur, Malaysia - Isti Hidayati; Claudia Yamu; Wendy Tan (Journal of Urban Management, 2021)
This article investigates how planning policies have shaped urban form and mobility behavior in the rapidly urbanized metropolitan area of Kuala Lumpur, Malaysia. We argue that the complex chain of consequences of previous policies and their implementation processes can be understood from the socio-spatial dynamics that result from the interaction between people and their built environment. Using the case of Kuala Lumpur, we provide empirical evidence of these socio-spatial dynamics through (1) the identification of key policies, (2) an understanding of Kuala Lumpur's spatial configuration using space syntax, and (3) in-depth interviews to reveal mobility behavior. Our findings suggest that Kuala Lumpur's previous road expansion policies, national car project, and fragmented new town development have created an urban form that encourages vehicular instead of pedestrian movement. Consequently, this has induced an automobile dependence and culture that conflicts with the country's current initiatives on sustainable development. For policymakers and planners, these findings provide awareness that policy impacts span across generations and scales, making them difficult to reverse and take a long time to be fixed. We conclude with practical insights on how to reverse the unsustainable path through socio-spatial innovations and research directions to address the ongoing vehicular dominance and automobile society in Kuala Lumpur.
Keywords: 710; Kuala lumpur; Mobility behavior; Planning policies; Space syntax; Urban form